Handbook of HPLC - Katz, Elena (Marcel Dekker, 1998)
The Handbook of HPLC discusses the principles, techniques, and instrumentation involving HPLC within a detailed, comprehensible framework—delineating its usage in separation, purification, and detection processes across a wide variety of disciplines from industry to applied research. Contains over 100 tables presenting previously scattered experimental data! Intended as an on-the-job guide for experienced practitioners as well as an invaluable introduction to the subject for novices, the Handbook of HPLC offers up-to-date information on fundamentals—ensuring the successful employment of HPLC with a solid grounding in essential theory methodology—assessing the limitations of reversed-phase HPLC, ion-exchange, size-exclusion HPLC, and other separation modes and showing how to select techniques that procure desirable results equipment—detailing the practical operation of pumps, detectors, injection devices, and data handling systems practices—exploring applications in areas such as pharmaceuticals, biotechnology, environmental monitoring, art conservation, nutrition, and food processing and more!
Chromatographic science series ; vol. 78
Keywords: chemie, klinická chemie; Chromatography, High Pressure Liquid; chromatografie; Chromatography; radiologie, nukleární medicína a zobrazovací metody; Chromatografie; vysokoúčinná kapalinová chromatografie